Assessment of fire blight resistance in apple clonal rootstocks using molecular markers - I. N. Shamshin; M. V. Maslova; N. V. Drenova; M. L. Dubrovsky; O. V. Parusova (Труды по прикладной ботанике, генетике и селекции)
Background. Clonal apple rootstocks are one of the main components of intensive gardening. The degree of rootstock damage by fire blight affects the resistance of the variety–rootstock combination. The paper presents a study on marking quantitative trait loci (QTL) of resistance to fire blight Erwinia amylovora in clonal apple rootstock.Materials and methods. A collection of 20 rootstock forms was analyzed. For the study, SCAR markers GE-8019, AE10-375 and microsatellite marker CH-F7-FB1 were used.Results. Polymorphism was observed for all three markers, and their various combinations in one genotype were revealed. It was previously noted that genotypes that carry all three markers were more resistant than those that lack them. The presence of all three markers was observed only in forms 62-396 (В10), 16-1 and 2-9-102. The other genotypes did not have the GE8019 marker. The AE10-375 marker was identified in eight clonal rootstocks. Microsatellite marker CH-F7-FB1 was present in all tested rootstocks. However, polymorphism was detected there. Most genotypes had a 174 bp fragment, but a 210 bp fragment was identified in two of the 20 forms. Clonal rootstock 70-20-21 proved heterozygous for this marker. The analyzed collection also included samples that had only the microsatellite marker: G16, Malysh Budagovskogo, Paradizka Budagovskogo (B9), 54-118 (В118), 57-491, 70-20-20 (В119), 70-20-21, 71-7-22, 76-3-6, 83-1-15, 87-7-12, and 2-12-10. The study of rootstock forms on the basis of resistance to metabolites of the fire blight pathogen was carried out under laboratory conditions using the E. amylovora culture filtrate in vitro on leaf explants. Most of the studied genotypes had different combinations of markers. However, the experiments showed that forms 62-396 and 14-1 with two out of three markers (AE10-375 and CH-F7-FB1) phenotypically manifested the trait of resistance to metabolites of E. amylovora.